2014
DOI: 10.1007/s11356-014-2798-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of PCDD/Fs in the metropolis of Istanbul, Turkey

Abstract: Atmospheric concentrations of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/F) compounds were investigated at three different regions of Istanbul which reflect urban, urban/industrial, and sub-urban characteristics. Air samples were collected simultaneously for both gaseous and particulate phases using high volume samplers on monthly time intervals from May 2011 to October 2012. The highest concentrations (3,056 fg/m(3) and 156 fg I-TEQ/m(3)) were observed at the sampling site that reflects traffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
0
7
0
1
Order By: Relevance
“…Monitoring of ambient air concentrations is then an important source of information in order to measure the evolution of these pollutants, depending on the location, meteorology variables (Gunes and Saral, 2014), mechanisms of transportation, deposition and dispersion (Castro Jimenez et al, 2011), or even seasonal parameters; it has been probed that the concentration of dioxins in ambient air is higher during winter months (Ding et al, 2013;Gunes and Saral, 2014;Wcgiel et al, 2014). Other important meteorological parameters that interact with dioxin concentrations are ultraviolet (UV), solar radiation, and precipitation.…”
Section: Worldwide Concentration Of Dioxinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Monitoring of ambient air concentrations is then an important source of information in order to measure the evolution of these pollutants, depending on the location, meteorology variables (Gunes and Saral, 2014), mechanisms of transportation, deposition and dispersion (Castro Jimenez et al, 2011), or even seasonal parameters; it has been probed that the concentration of dioxins in ambient air is higher during winter months (Ding et al, 2013;Gunes and Saral, 2014;Wcgiel et al, 2014). Other important meteorological parameters that interact with dioxin concentrations are ultraviolet (UV), solar radiation, and precipitation.…”
Section: Worldwide Concentration Of Dioxinsmentioning
confidence: 99%
“…Table 1 represents some gathered data by different reviews, where different ambient concentrations in Europe are shown (expressed in I-TEQ Table 1. Ambient air concentrations in Europe: (A) Lohmann and Jones (1998); (B) Mari et al (2008); (C) Gunes and Saral (2014) It can be seen in Table 1 that industrial locations have the highest peaks of concentrations, followed by urban, rural, and remote sites, although this does not imply that industrial areas have implicit dangerous levels of air concentrations, if proper measures are established (Abad et al, 2007;Li et al, 2010). Although Table 1 only refers to air concentrations, the same differences between different location areas can be extended to soils pollution, with higher concentrations for urban samples than for rural ones (Creaser et al, 1990;Urban et al, 2014).…”
Section: Dioxins In Europementioning
confidence: 99%
See 1 more Smart Citation
“…Concentration of airborne PCDD/F depends on many factors, like pollution sources, strength and direction of convective air flows, air trajectories, atmospheric deposition [33,38] and meteorological conditions (temperature, wind speed, wind direction, barometric pressure and humidity). For the measuring of meteorological conditions, we used the Magellan vehicle-mount mobile weather station.…”
Section: Assessment Of Meteorological Conditionsmentioning
confidence: 99%
“…In Lithuania, according to the data of 2016, about 30 percent of waste is landfilled, 5 percent is stored, 48 percent is recycled, and 17 percent is burned (EUROSTAT). The amount of PCDD/F in ambient air is higher in winter season [32][33][34]. Thus, a monitoring of the PCDD/F emissions in atmosphere is an important factor while trying to assess concentration of pollutants depending on location, meteorological parameters [31], transport mechanisms, sedimentation and dispersion [35] or even seasonal changes.…”
Section: Introductionmentioning
confidence: 99%